Mutations in mitochondrial ferredoxin FDX2 suppress frataxin deficiency - Joshua D. Meisel; Pallavi R. Joshi; Amy N. Spelbring; Hong Wang; Sandra M. Wellner; Presli P. Wiesenthal; Maria Miranda; Jason G. McCoy; David P. Barondeau; Gary Ruvkun; Vamsi K. Mootha (Nature, 2026)
Abstract Frataxin is a key component of an ancient, mitochondrial iron–sulfur cluster biosynthetic machinery, serving as an allosteric activator of the cysteine desulfurase NFS1 (refs. 1–5 ). Loss of frataxin levels underlies Friedreich’s ataxia 6 , the most common inherited ataxia. Yeast, C aenorhabditis elegans and human cells can tolerate loss of frataxin when grown in ‘permissive’ low oxygen tensions 7 . Here we conducted an unbiased, genome-scale forward genetic screen in C. elegans leveraging permissive and non-permissive oxygen tensions to discover suppressor mutations that bypass the need for frataxin. All mutations act dominantly and are in the ferredoxin FDX2 / fdx-2 or in the cysteine desulfurase NFS1 / nfs-1 genes, resulting in amino-acid substitutions at the FDX2–NFS1 binding interface. Our genetic and biochemical analyses show that the suppressor mutations boost iron–sulfur cluster levels in the absence of frataxin. We also demonstrate that an excess of FDX2 inhibits frataxin-stimulated NFS1 activity in vitro and blocks the synthesis of iron–sulfur clusters in mammalian cell culture. These findings are consistent with structural and biochemical evidence that frataxin and FDX2 compete for occupancy at the same site on NFS1 (refs. 8,9 ). We show that lowering levels of wild-type FDX2 through loss of one gene copy can ameliorate the growth of frataxin mutant C. elegans or the ataxia phenotype of a mouse model of Friedreich’s ataxia under normoxic conditions. These genetic and biochemical studies indicate that restoring the stoichiometric balance of frataxin and FDX2 through partial knockdown of FDX2 may be a potential therapy for Friedreich’s ataxia.